Marathon running increases circulating endothelial- and thrombocyte-derived microparticles. (February 2018) - Schwarz, Viktoria; Düsing, Philip; Liman, Thomas; Werner, Christian; Herm, Juliane; Bachelier, Katrin; Krüll, Matthias; Brechtel, Lars; Jungehulsing, Gerhard J; Haverkamp, Wilhelm; Böhm, Michael; Endres, Matthias; et al.
Background: Acute vascular effects of high intensity physical activity are incompletely characterized. Circulating microparticles are cellular markers for vascular activation and damage. Methods: Microparticles were analysed in 99 marathon runners (49 ± 6 years, 22% female) of the prospective Berlin Beat of Running study. Blood samples were taken within three days before, immediately after and within two days after the marathon run. Endothelial-derived microparticles were labelled with CD144, CD31 and CD62E, platelet-derived microparticles with CD62P and CD42b, leukocyte-derived microparticles with CD45 and monocyte-derived microparticles with CD14. Results: Marathon running induced leukocytosis (5.9 ± 0.1 to 14.8 ± 0.3 10 9 /l, p  < 0.0001) and increased platelet counts (239 ± 4.6 to 281 ± 5.9 10 9 /l, p  < 0.0001) immediately after the marathon. Blood monocytes increased and lymphocytes decreased after the run ( p  < 0.0001). Endothelial-derived microparticles were acutely increased ( p  = 0.008) due to a 23% increase of apoptotic endothelial-derived microparticles ( p  = 0.007) and returned to baseline within two days after the marathon. Thrombocyte-derived microparticles acutely increased by 38% accompanied by an increase in activated and apoptotic thrombocyte-derived microparticles ( p  ≤ 0.0001) each. Both monocyte- and leukocyte-derived microparticles were decreased immediately after marathon run ( p  < 0.0001) and remained below baseline until day 2. Troponin T increased from 12 to 32 ng/l ( p  < 0.0001) immediately after the run and returned to baseline after two days. Conclusion: Circulating apoptotic endothelial- and thrombocyte-derived microparticles increased after marathon running consistent with an acute pro-thrombotic and pro-inflammatory state. Exercise-induced vascular damage reflected by microparticles could indicate potential mechanisms of post-exertional cardiovascular complications. Further studies are warranted to investigate microparticles as markers to identify individuals prone to such complications.